Dual Organic Spacer Cation Quasi‐2D Sn–Pb Perovskite for Solar Cells and Near‐Infrared Photodetectors Application. Issue 9 (29th May 2022) - Wang, Ya; Lin, Xiaoyun; Zhou, Renlai; Chen, Tong; Lou, Qiang; Li, Qian; Zhou, Hang
Abstract : Tin (Sn)‐ and Sn–Pb‐based perovskites arouse great interests in low‐toxicity perovskite. Nevertheless, the instability problems that aroused by Sn oxidation still hinder their applications. To improve the stability of Sn‐based perovskite, a relative stable quasi‐2D Sn–Pb perovskite is proposed by introducing two mixed organic cations, 2‐phenylethylammonium (PEA + ), and butylammonium (BA + ), which facilitate both precursor assembly and carrier transportation. As a result, efficient and stable quasi‐2D Sn–Pb perovskite solar cells (PSCs) with a power conversion efficiency (PCE) of ≈10% and an improved open‐circuit voltage ( V oc ) of 0.808 V under AM 1.5G illumination are achieved. The maximum power point (MPP) shows that the current of quasi‐2D Sn–Pb PSC still maintains 97.7% of original value after 20 000 s. Furthermore, the application of the mixed spacer cation quasi‐2D Sn–Pb perovskite in near‐infrared (NIR) light detection is demonstrated. Herein, the quasi‐2D Sn–Pb perovskite shows a high detectivity of ≈6.57 × 10 11 Jones with n–i–p structure under 850 nm. It is suggested in the results that the quasi‐2D Sn–Pb perovskite with improved stability holds great potential in infrared photodetection and imaging application. Abstract : Herein, quasi‐2D Sn–Pb perovskite with mixed 2‐phenylethylammonium (PEA + ) and butylammonium (BA + ) cations exhibits an absorption spectrum extended to 1000 nm. Solar cells based on this quasi‐2D perovskite present high stability, with a power conversion efficiency (PCE) of ≈10% and an open‐circuit voltage (Voc) of 0.808 V. When applied as near infrared (NIR) photodetectors, they show detectivities of ≈10 11 Jones both in n‐i‐p and p‐i‐n device configuration.